The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s1677-04202008000200005
|View full text |Cite
|
Sign up to set email alerts
|

Salinity effects on leaf ion composition and salt secretion rate in Avicennia germinans (L.) L.

Abstract: The effect of salinity on leaf water relations, and rate and ionic composition of leaf secretion was investigated in plants of Avicennia germinans growing under controlled salinity conditions. Increases in salinity from 0 to 940 mol NaCl m -3 reduced the predawn water potential from -0.56 to -4.16 MPa and the solute potential from -2.27 to -4.48 MPa, whereas the pressure potential remained positive in all treatments. Compared to the control, at 940 mol NaCl m -3 Na + and Cl -concentrations of leaf sap increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 34 publications
4
18
0
Order By: Relevance
“…Different letters in the same column are significantly different at P < 0.05 level, as determined by DMRT sary for maintaining the turgor pressure (Navarro et al 2003). Through the analysis of water relations in the leaves of S. argentea, we observed that plants adjusted their Ψ w to more negative levels as salinity increased (Figure 1), which is a common reaction to salinity similar to those reported for other species (Navarro et al 2003, Suárez andMedina 2008). Significant reduction of RWC in leaves of plants treated with 400 and 600 mmol/l (Figure 1) indicated that salinity also resulted in dehydration at cellular level and dehydration symptoms were greater in higher NaCl concentration treatment because of the increasing cellular water loss.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Different letters in the same column are significantly different at P < 0.05 level, as determined by DMRT sary for maintaining the turgor pressure (Navarro et al 2003). Through the analysis of water relations in the leaves of S. argentea, we observed that plants adjusted their Ψ w to more negative levels as salinity increased (Figure 1), which is a common reaction to salinity similar to those reported for other species (Navarro et al 2003, Suárez andMedina 2008). Significant reduction of RWC in leaves of plants treated with 400 and 600 mmol/l (Figure 1) indicated that salinity also resulted in dehydration at cellular level and dehydration symptoms were greater in higher NaCl concentration treatment because of the increasing cellular water loss.…”
Section: Discussionsupporting
confidence: 83%
“…The main negative effects of high salinity that influence plant growth and development are photosynthesis inhibition (Sharma et al 2005), water deficit (Suárez and Medina 2008), ion toxicity associated with excessive Cl -and Na + (Afzal et al 2008, Patel andPandey 2008), interference with nutrition leading to nutrient imbalance (Misra et al 1997). Bastías et al (2004) have reported that high concentrations of salt disrupt homeostasis in water relations and change the ion distribution at both cellular and whole plant levels.…”
mentioning
confidence: 99%
“…Decreasing external water potential produces a net accumulation of solutes in cells, which lowers the cell osmotic potential necessary for maintaining the turgor pressure (Suárez and Medina, 2008). An interesting observation of this study was that plants inoculated with PGPR in normal as well as under salinity have greater RWC and cell membrane stability which is accordance with Sandhya et al (2010).…”
Section: Discussionmentioning
confidence: 99%
“…Further effect of salinity stress was explained by Kanai et al (2014) which showed a decreasing growth rate of mangrove under salinity stress. High salinity decreased the leaf half-life of mangrove (Suárez & Medina, 2008). Thus, it can be concluded that mangrove which grows in the saline environment has a lower growth rate compared to mangroves in the less saline environment.…”
Section: Resultsmentioning
confidence: 89%